2000
DOI: 10.1021/la0007933
|View full text |Cite
|
Sign up to set email alerts
|

Highly Viscoelastic Wormlike Micellar Solutions Formed by Cationic Surfactants with Long Unsaturated Tails

Abstract: Cationic surfactants having long (C22) mono-unsaturated tails were studied in aqueous solutions containing salt using steady and dynamic rheology. The surfactant erucyl bis(hydroxyethyl)methylammonium chloride self-assembles into giant wormlike micelles, giving rise to unusually strong viscoelasticity. Under ambient conditions, the viscosity enhancement due to surfactant exceeds a factor of 107. Some samples behave as gel-like solids at low temperatures and revert to the viscoelastic (Maxwellian) response only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
440
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(503 citation statements)
references
References 27 publications
58
440
2
3
Order By: Relevance
“…In particular, as temperature increases, the viscosity initially rises to an inflection point then begins degrading afterward and this process can repeat at higher temperatures (Rabie and Nasr-El-Din 2015). This viscosity ''enhancement'' suggests that not all of the micelles entangled to form wormlike micelles at low temperatures (Raghavan and Kaler 2001). As temperature increases, the wormlike micelles grow to a lesser extent thereby reducing the micellar length and leading to a decrease in rheological properties .…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, as temperature increases, the viscosity initially rises to an inflection point then begins degrading afterward and this process can repeat at higher temperatures (Rabie and Nasr-El-Din 2015). This viscosity ''enhancement'' suggests that not all of the micelles entangled to form wormlike micelles at low temperatures (Raghavan and Kaler 2001). As temperature increases, the wormlike micelles grow to a lesser extent thereby reducing the micellar length and leading to a decrease in rheological properties .…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The length and composition of the tail are of primary importance when it comes to altering rheological properties of the solution (Raghavan and Kaler 2001). In this case, surfactants with coco-based tails, such as ARM and ECA, typically contain 12-16 carbon atoms, while surfactants with tallow-based tails, such as DTTM and EDM, consist of 14-18 carbons.…”
Section: Tail Group Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wormlike micelles are known to mutually entangle to form a gel with a high viscoelasticity, which arises due to the formation of a transient network structure. It is already known that worm-like micelles can be formed by the addition of aromatic salts such as sodium salicylate to cationic surfactants such as cetyltrimethylammonium bromide or cetylpyridinium chloride [1][2][3][4] . Recently, Kunieda et al [5][6][7][8] reported that a worm-like micelle of high viscoelasticity was formed by mixing two types of nonionic surfactants with very different HLB (hydrophilic-lipophilic balance) values.…”
Section: Introductionmentioning
confidence: 99%
“…Raghavan et al 4) examined the influence of temperature on the rheological properties of worm-like micelles, and they clarified that worm-like micelles formed from ionic surfactants typically show an exponential decrease in zeroshear viscosity (h 0 ) upon heating. However, there were few reports about the temperature behavior of worm-like micelles consisting of nonionic surfactants 10,11) .…”
Section: Introductionmentioning
confidence: 99%